Organizational Structure, Cross-functional Integration and Performance of New Product Development Team. (2017) - Bai, Wenxiao; Feng, Yicheng; Yue, Yunju; Feng, Lijie
Abstract: In the era of global competition, how to improve the performance of new product development team is an important scientific issue. In this study, with the organizational structure of the enterprise as the explanatory variable, the cross-functional integration of the team as the intermediary variable, a cross level conceptual model is constructed to analyze the performance of new product development team, and the survey data of manufacturing industry and high-tech industry in China are analyzed by using multilevel linear model. The research results show that the characteristics of organizational structure has impact of cross levels on performance of new product development team, cross-functional integration of the team has a partial mediating effect between the mechanical organization and the performance of the new product development team and a complete mediating effect between the organic organization and the performance of the new product development team.